The Effect of Neoadjuvant Chemotherapy on HIF-1α Expression in Cervical Uterine Cancer - Wiraswesty, Ika; Respati, Supriyadi Hari; Sulistyowati, Sri; Priyanto, Heru (Indonesian Journal of Medicine, 2018)
Background: Uterine cervical cancer is one of the main causes of female death related to cancer. Neoadjuvant chemotherapy aims to reduce tumor mass to allow radical surgery. HIF-1α is thought to have a key role in the development of cancer and the main target for chemoprevention.Objective: This study aims to prove the effect of neoadjuvant chemotherapy on HIF-1α expression in uterine cervical cancer as an assessment parameter for chemotherapy response. Subjects and methods: The study was carried out in the Department of Obstetrics and Gynecology and the Pathology Department of Anatomy Dr. Moewardi - Faculty of Medicine, Sebelas Maret University, Surakarta. Thirty (30) cervical cancer samples that met the inclusion and exclusion criteria were examined for HIF-1α expression before and after giving 3 times neoadjuvant chemotherapy. Examination using immunohistochemical methods. Data analysis using t-test.Results: Mean HIF-1α expression before administration of neoadjuvant chemotherapy 5.10± 1.174 cell/field, after administration of neoadjuvant chemotherapy 4.00±1.174 cell/field with p=0.001.Conclusion: Neoadjuvant chemotherapy has an effect on reducing HIF-1α expression in uterine cervical cancer.Keywords: neoadjuvant chemotherapy, HIF-1α, uterine cervical cancerCorrespondence: Sri Sulistyowati. Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Sebelas Maret. Mobile: 08122968215. email: elis_spog@yahoo.co.id Indonesian Journal of Medicine (2018), 3(2): 119-124https://doi.org/10.26911/theijmed.2018.03.02.08